The interrelation of EU law with inter se international agreements of the EU member states - Georgaki, K; Eleftheriadis, P (2021)
This thesis examines how EU law interrelates with international agreements concluded between EU Member States inter se when a conflict between their norms can be identified. Chapter One starts by distinguishing between the different types of international agreements that may co-exist with EU law and argues that conflicts between EU law and inter se agreements need to be approached as conflicts of treaty norms on the international plane, using the conflict avoidance techniques and conflict resolution rules of international law. Against this background, Chapter Two examines and discards the premise that EU law constitutes a ‘new legal order’, highlighting the nature of EU law as international law. Chapter Three then examines the position of EU law within international law, identifying EU law as an autonomous sub-system within public international law, in the sense of a broadly conceived ‘self-contained regime’. Chapter Four moves on to define the notion of ‘conflict’ between EU law and inter se agreements and provides the conceptual framework, within which it is to be grasped. Chapter Five explores the available conflict avoidance techniques, identifying two interrelated, yet distinct interpretative methods applicable to the context of this thesis: first, the principle of systemic integration, enshrined in Article 31(3)(c) of the Vienna Convention on the Law of Treaties (VCLT); and second, the principle of a consistent-with-EU-law interpretation of inter se agreements, as a special application of the principle of harmonious interpretation applied in international law. Finally, Chapter Six identifies the rules governing conflict resolution in the interrelation of EU law with inter se agreements: first, Article 59 VCLT on the implicit abrogation of an earlier agreement by the conclusion of a later one between the same contracting parties; second, Article 30 VCLT, to the extent that it codifies the pacta tertiis principle of public international law; and third, the principle of primacy of EU law, which operates as a lex specialis, carving out the lex posterior conflict rule enshrined in Articles 30(3) and 30(4)(a) VCLT.